1986
DOI: 10.1103/physreva.33.3742
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic electronic-structure calculations employing a two-component no-pair formalism with external-field projection operators

Abstract: A no-pair formalism employing external-field projection operators correct to second order in the potential is used to calculate the 1s energies of one-electron atoms and ground-state properties of the bromine and silver atoms in the framework of the multireference double-excitation configurationinteraction (MRD-CI) method. It is found that the relativistic two-component method that has been used reproduces the one-particle energies of the Dirac equation to order (Za)'. The operator is bounded from below and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1,483
0
3

Year Published

1997
1997
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,341 publications
(1,535 citation statements)
references
References 26 publications
3
1,483
0
3
Order By: Relevance
“…When BS1d and BS1t were used as basis sets, relativistic effects were accounted for using a Douglas-Kroll-Hess Hamiltonian. 87, 88 The performance of the CASSCF/CASPT2 model, which has been widely used for the quantitative modeling of various aspects of transition-metal chemistry, [89][90][91] depends critically on the choice of the orbital active space for the CAS reference. In our earlier work focusing on the µ-η 2 :η 2 peroxo/bis(µ-oxo) equilibrium, 28 we found that no accessible active space gave a satisfactory description of all structures along the isomerization coordinate.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…When BS1d and BS1t were used as basis sets, relativistic effects were accounted for using a Douglas-Kroll-Hess Hamiltonian. 87, 88 The performance of the CASSCF/CASPT2 model, which has been widely used for the quantitative modeling of various aspects of transition-metal chemistry, [89][90][91] depends critically on the choice of the orbital active space for the CAS reference. In our earlier work focusing on the µ-η 2 :η 2 peroxo/bis(µ-oxo) equilibrium, 28 we found that no accessible active space gave a satisfactory description of all structures along the isomerization coordinate.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…18 Scalar relativistic effects were included using a Douglas-Kroll (DK) Hamiltonian. 19,20 The effects of spin-orbit (SO) coupling were introduced using a newly developed method based on the CASSCF State Interaction approach (CASSI), 21,22 Here, the CASSCF wave function generated for a number of electronic states are allowed to mix under the influence of a spin-orbit Hamiltonian. The method has recently been described, 16 and we refer to this article for details.…”
Section: Methods and Details Of The Calculationsmentioning
confidence: 99%
“…18,19 All the calculations were performed using the MOLCAS software. 20 In a first step we perform state-average complete active space self-consistent-field calculations (SA-CASSCF).…”
Section: Scalar Relativistic and Spin-orbit Coupling Calculationsmentioning
confidence: 99%